2014
DOI: 10.1002/jbm.b.33296
|View full text |Cite
|
Sign up to set email alerts
|

Comparative local immunogenic potential of scaffolds prepared from porcine cholecyst, jejunum, and urinary bladder in rat subcutaneous model

Abstract: Extracellular matrices isolated from several mammalian organs/tissues have found several clinical uses as xenografts or implants. However, they may cause complications because of adverse immunologic reactions. Scaffolds that promote favorable graft-acceptance reaction are preferred for fabricating xenografts. The objective of this study was to evaluate the immunogenic potential of a porcine cholecyst-derived scaffold (CDS), prepared by a non-detergent/enzymatic method, in comparison with jejunum and urinary bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 39 publications
3
22
0
Order By: Relevance
“…The CDE contained at least 154 proteins, whereas JDE had 186 proteins indicating the diversity of detectable proteins in the respective extracts. Of these, 79% proteins in CDE and 90% proteins in JDE were of cellular in origin (Table ), possibly indicating the rarity of cell debris in CDE . The finding is not surprising and it is known that even after rigorous decellularization procedures involving, detergents, enzymes, and/or decontaminating agents are not expected to cause complete removal of cellular residue .…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…The CDE contained at least 154 proteins, whereas JDE had 186 proteins indicating the diversity of detectable proteins in the respective extracts. Of these, 79% proteins in CDE and 90% proteins in JDE were of cellular in origin (Table ), possibly indicating the rarity of cell debris in CDE . The finding is not surprising and it is known that even after rigorous decellularization procedures involving, detergents, enzymes, and/or decontaminating agents are not expected to cause complete removal of cellular residue .…”
Section: Discussionmentioning
confidence: 93%
“…Despite these drawbacks, the study indicated the relative absence of immunogenic proteins in the ECM of cholecyst that can cause adverse host reactions. This sparse content of protein load might have contributed for the lower immunogenic potential of CDS in comparison with scaffolds prepared from jejunum …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The method has been used for preparing tissue engineering scaffolds from porcine cholecyst (gall bladder), jejunum (small intestine), and urinary bladder. When these scaffolds were used as a subcutaneous graft (Muhamed, Revi, Rajan, & Anilkumar, ) or as a skeletal muscle graft (Balakrishnan‐Nair et al, ), the scaffold prepared from cholecyst known as cholecyst derived scaffold (CDS) promoted an anti‐inflammatory tissue remodeling response rather than a graft rejection reaction in animal models, indicating the possibility of using the CDS as scaffolds for fabricating tissue constructs. On the other hand, the bioinductive properties of any material are known to compromise with exposure to higher concentration of cross‐linking agent (Sart et al, ).…”
Section: Introductionmentioning
confidence: 99%